Introduction of a bone-centered three-dimensional coordinate system enables computed tomographic canine femoral angle measurements independent of positioning - Brühschwein, Andreas; Schmitz, Bronson; Zöllner, Martin; Reese, Sven; Meyer-Lindenberg, Andrea (Frontiers in Veterinary Science, 2022)
Introduction Measurement of torsional deformities and varus alignment in the canine femur is clinically and surgically important but difficult. Computed tomography (CT) generates true three-dimensional (3D) information and is used to overcome the limitations of radiography. The 3D CT images can be rotated freely, but the final view for angle measurements remains a subjective variable decision, especially in severe and complex angular and torsional deformities. The aim of this study was the development of a technique to measure femoral angles in a truly three-dimensional way, independent of femoral positioning. Methods To be able to set reference points in any image and at arbitrary positions of the CT series, the 3D coordinates of the reference points were used for mathematical calculation of the angle measurements using the 3D medical imaging Software VoXim®. Anatomical reference points were described in multiplanar reconstructions and volume rendering CT. A 3D bone-centered coordinate system was introduced and aligned with the anatomical planes of the femur. For torsion angle measurements, the transverse projection plane was mathematically defined by orthogonality to the longitudinal diaphyseal axis. For varus angle measurements, the dorsal plane was defined by a femoral retrocondylar axis. Independence positioning was tested by comparison of angle measurement results in repeated scans of 13 femur bones in different parallel and two double oblique (15/45°) positions in the gantry. Femoralvarus (or valgus), neck version (torsion), and inclination angles were measured, each in two variations. Results Resulting mean differences ranged between –0.9° and 1.3° for all six determined types of angles and in a difference of <1° for 17 out of 18 comparisons by subtraction of the mean angles between different positions, with one outlier of 1.3°. Intra- and inter-observer agreements determined by repeated measurements resulted in coefficients of variation for repeated measurements between 0.2 and 13.5%. Discussion The introduction of a bone-centered 3D coordinate system and mathematical definition of projection planes enabled 3D CT measurements of canine femoral varus and neck version and inclination angles. Agreement between angular measurements results of bones scanned in different positions on the CT table demonstrated that the technique is independent of femoral positioning.